PERAN TEKNOLOGI DALAM PENGENDALIAN PENCEMARAN LINGKUNGAN HIDUP - Herlambang, Arie (BPPT)
Basically, nature has the ability to perform the restoration of environmental damage caused by increased human activity, but because of the limited carrying capacity, then the environment has decreased the quality from year to year. In saving the environment, technology plays a role in reducing the risk of pollution, increased efi siensi process, and creating processes and environmentall friendly products, monitoring and prediction of environment quality, environmental pollution control, restoration and environmental improvement. Waste Technology (end of pipe technology) are widely used to cope with environmental pollution, both for liquid waste, solid and air. Waste processing technology developed for the waste can be in accordance with quality standards thathave been established, while monitoring technology has been developed either manually or automatically. For recovery and improvement of technology has been developed remedies and restoration that rely on bacteria in nature.Keywords: end of pipe technology, reuse, recycle, reduce (3R), carrying capacity, and environment pollution